Are Soccer Players Older Now Than Before? Aging Trends and Market Value in the Last Three Decades of the UEFA Champions League - Kalén, Anton; Rey, Ezequiel; de Rellán-Guerra, Alejandro Sal; Lago-Peñas, Carlos (Frontiers in Psychology, 2019)
The aims of the current study were to analyze the evolution of players’ age in the UEFA Champions League since the start of its modern-day format in 1992-93 up until 2017-18 and to determine how the players’ age relates to their market value. The sample consisted of all players participating in the UEFA Champions League from the 1992-93 to 2017-18 seasons (n = 16062). The following variables were used in this study: players’ age, number of seasons in the club, number of Champions Leagues won, team performance, and market value of the player in the season. Data were examined using a one-way ANOVA and a linear regression. The main finding of the current study is that an aging trend has occurred in the last three decades in the Champions League. A significant increase in average players’ age (> 1.6 years) was observed, rising from an age of 24.9 to 26.5 years. Goalkeepers and Center Backs tend to peak later than attackers, and their peak performance can last until an age of about 31 years. Finally, an inverted-U curve characterizes the relationship between market value and age, with peak value occurring in the 26-30 age range. These results provide useful information in terms of informing our expectations about when soccer players are likely to perform at the maximum level. They also inform us about when they are likely to be the most valuable in the market.